Histopathological correlates of basal cell carcinoma in the slice and en face imaging modes of high‐definition optical coherence tomography. (June 2014) - Gambichler, T.; Plura, I.; Kampilafkos, P.; Valavanis, K.; Sand, M.; Bechara, F.G.; Stücker, M.
Summary Background High‐definition optical coherence tomography (HD‐OCT) scanners have recently been developed, providing significantly higher resolution than conventional OCT. Objectives To assess the relationship between recently defined histopathological HD‐OCT correlates of basal cell carcinomas (BCC) and possible predictors for the most common tumour subtypes. Methods For HD‐OCT imaging, we used the Skintell® device. Twenty‐five BCCs were histopathologically confirmed (including both vertical and horizontal haematoxylin and eosin and Alcian blue sectioning) and correlated with HD‐OCT images. Results In the en face mode, lobulated nodules were seen in 21/25 BCCs (84%), peripheral rimming in 18/25 (72%), epidermal disarray in 18/25 (72%) and variably refractile stroma in 22/25 (88%). In the slice imaging mode, we observed destruction of layering in 19/25 (76%) BCCs. In both the slice and en face modes a significant correlation was observed between peritumoral rimming and grey/dark oval structures and lobulated nodules. Alcian blue stains showed peritumoral mucin deposits correlating with peripheral rimming around the tumour nodules. In a logistic regression model, we did not observe significant independent micromorphological HD‐OCT predictors for either the solid or superficial BCC subtypes. Conclusions In agreement with recent studies we have demonstrated that HD‐OCT using the slice and en face imaging modes can visualize histopathological correlates of BCC, and potentially aid noninvasive diagnostics. However, using HD‐OCT correlation it was not possible to predict the superficial or solid BCC subtypes. For the first time we have shown that peripheral rimming in HD‐OCT correlates with peritumoral mucin deposition.